Computers and languages : theory and practice - Nijholt, Anton, 1946- (Studies in computer science and artificial intelligence, 1988)
A global introduction to language technology and the areas of computer science where language technology plays a role. Surveyed in this volume are issues related to the parsing problem in the fields of natural languages, programming languages, and formal languages.